The Use of Contextualized Activities on Acquisition of Chemistry Concepts in Science - Gecolea, Cincy Merly; Amon, Ma. Fe Lorelei E. (International Journal of Research in STEM Education, 2022)
The study of chemistry is considered to be the most important discipline of study because of its significant impact on both the individuals who study it and society as a whole. Because of this, many academicians now believe it to be an important area of study. This study mainly focused on the use of contextualized activities in the acquisition of Chemistry concepts in Science7. Quasi-experimental, particularly the non-equivalent dependent variable, was utilized as the research design. The scores during pre- and post-tests served as the primary source of data from the 41 Grade 7 students. Total enumeration was implemented. The study revealed that there is a significant difference in the results of the pre-test and post-test of the Grade 7 students since the calculated t-value (52.84) exceeded the critical value (2.02). The scope and focus of the study were limited only to the use of contextualized activities intended to determine its effects on the acquisition of Chemistry concepts in Science 7. It was also restricted only to 41 students of the Calamba Bayside National High School who are enrolled in the school year 2017-2018. The results of the study could help the division in encouraging teachers to be more creative and innovative and craft more contextualized learning materials in science.